Off Clamping Laparoscopic Resection of An Extreme Rare Renal Mesenchymal Tumor: An Angiomyolipoma of Renal Capsule - Simforoosh, Nasser; Bonakdar Hashemi , Milad; Aslani, Arsalan; Mohammadzadeh, Sahand (Urology Journal, 2021)
Renal mesenchymal tumors are described as neoplasms with vascular, fibrous, and adipose tissues. The renal lipoma is an extremely rare renal mesenchymal tumor, typically originating from renal capsule and it is usually presented as well circumscribed homogenous fat containing mass. Angiomyolipoma (AML) is the most common benign mesenchymal renal tumor which is composed of mature epithelioid cells. The renal AML usually presented as exophytic, non-infiltrative, and fat contain tumor. The well differentiated renal retroperitoneal liposarcoma and lipoma seem to be misdiagnosed by exophytic renal angiomyolipoma but the renal AML usually arises from renal parenchyma with characteristic images. A 37-year-old woman came to our clinic with rapid growth renal mass and pain. The spiral abdominopelvic computed tomography scan (CT-scan) showed well-circumscribed hypoheterodense fat-containing mass near to middle pole of the right kidney with minimal fat stranding without neovascularity and cortical defect. The Patient underwent off-clamping laparoscopic resection of renal mass with pre-operative impression: liposarcoma versus lipoma of the kidney. The cross-section of the surgical specimen revealed irregular lobulated fatty tissue with hemorrhagic streaks. Definite diagnosis was made by immunohistochemistry study. Spindle cells and epithelioid cells are diffusely and strongly positive for α-smooth muscle actin. The perivascular cells and epithelioid cells are positive for HMB-45 and Melanin. The immunostaining pattern was compatible with angiomyolipoma that originated from renal capsule. In our experience, a rapid growing mass that is accompanied by pain draws the attention to malignant process. The renal AML rarely arises from renal capsule without characteristic images so having high doubt may lead to proper pre-operative diagnosis.